Study on wage rigidity in Brazil - Jeong, Hyeon Jin (2022)
This study investigates the nominal and real wage rigidities in the Brazilian formal labor market. It explores two features of nominal wage rigidity: first, the existence of a certain nominal wage raise rate in which a great number of employees experience in each year; and, second, the stickiness of nominal wage. It uses three different indicators to calculate nominal wage rigidity and survival analysis is conducted to analyze nominal wage stickiness. This study provides empirical evidence for the benchmark used by collective bargaining negotiators to nominal wage raise. One additional finding is that different entities - unions and firms - do not influence the collective negotiation results.